Majority and popularity effects on norm formation in adolescence - Ana da Silva Pinho (Nature Portfolio, 2021)
Abstract Personal norms consist of individuals’ attitudes about the appropriateness of behaviour. These norms guide adolescents’ behaviour in countless domains that are fundamental for their social functioning and well-being. Peers are known to have a marked influence on adolescent risk-taking and prosocial behaviour, but little is known about how peers shape personal norms underlying those behaviours. Here we show that adolescents’ personal norms are decisively moulded by the norms of the majority and popular peers in their social network. Our experiment indicates that observing peer norms substantially impacts adolescents’ normative evaluation of risk-taking and prosocial behaviours. The majority norm had a stronger impact than the norm of a single popular peer, and norm adjustments were largest when adolescents observed strong disapproval of risk-taking or strong approval of prosocial behaviour. Our study suggests that learning about peer norms likely promotes adolescents to hold views and values supporting socially desirable behaviour.